2005
DOI: 10.1542/peds.2004-1550
|View full text |Cite
|
Sign up to set email alerts
|

Immersion Scald Burns and the Ability of Young Children to Climb Into a Bathtub

Abstract: Our study may have underestimated children's climbing abilities because of the absence of a shower curtain to help with balance and the distracting presence of strangers. The diagnosis of abuse is in part based on a described mechanism being inconsistent with the observed pattern of injury. This has severe repercussions for the child and his or her family. Our study brings into question previously held beliefs that these injuries could only be sustained by direct immersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Their study concluded that children do have the ability to climb into the bathtub and could potentially burn themselves. 12 Thombs et al at the Johns Hopkins Institute analyzed burn injuries using the national burn registry from 1992 to 2002. Their study concluded that children less than 4 years of age are at highest risk of injuries, mainly scalds.…”
Section: Discussionmentioning
confidence: 99%
“…Their study concluded that children do have the ability to climb into the bathtub and could potentially burn themselves. 12 Thombs et al at the Johns Hopkins Institute analyzed burn injuries using the national burn registry from 1992 to 2002. Their study concluded that children less than 4 years of age are at highest risk of injuries, mainly scalds.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, as many as 35% of typically developing children aged 10 to 18 months can climb into a bathtub. 70 Therefore, the primary problem for this young age group is lack of barriers to prevent unanticipated, unsupervised access to water, including swimming pools, hot tubs and spas, bathtubs, natural bodies of water, and standing water in homes (buckets, tubs, and toilets). The CPSC found that 69% of children younger than 5 years were not expected to be at or in the pool at the time of a drowning incident.…”
Section: Toddlersmentioning
confidence: 99%
“…In a recent study, 2 we reported on the ability of children aged 10 to 18 months to independently climb into a standard bathtub. A standard bathtub was installed in an examination room in the General Pediatric Clinic of Children's Hospital of Michigan.…”
Section: To the Editormentioning
confidence: 99%